Development and some applications of enzyme-linked immunosorbent assay system for murine macrophage inflammatory protein-2 (MIP-2) - H. Ochiai; S. Sakai; T. Kogure; T. Hirabaytashi; K. Nakajima; K. Terasawa (Mediators of Inflammation)
We attempted to establish an enzyme-linked immunosorbent assay (ELISA) system by preparation of recombinant murine MIP-2 and its rabbit antibodies. A fusion construct of MIP-2 to protein A was used to enable easy purification as well as the generation of a sufficiently large antibody response. The specificity of antibody was confirmed by Western blotting analysis of 20-h conditioned medium from lipopolysaccharide (LPS)-stimulated RAW264.7 cells, a murine macrophage cell line; antibody gave a single band with a molecular weight of approximately 6000, which is identical to that of murine MIP-2 reported previously. Biotin–streptavidin sandwich ELISA could detect quantitatively MIP-2 at concentration range of 20 to 1000 pg/ml. In some applications of this ELISA system, time-related production of MIP-2 and inhibitory effect of dexamethasone on its production have been demonstrated in LPS-stimulated RAW264.7 cells. Thus, ELISA system established in this study is considered to be a useful tool to study MIP-2 response in various inflammation models in mice.